2014
DOI: 10.1021/bm401822p
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Assembly of β-Sheet Nanocrystals within Caddisfly Silk

Abstract: Nuclear magnetic resonance (NMR) and X-ray diffraction (XRD) experiments reveal the structural importance of divalent cation–phosphate complexes in the formation of β-sheet nanocrystals from phosphorylated serine-rich regions within aquatic silk from caddisfly larvae of the species Hesperophyla consimilis. Wide angle XRD data on native caddisfly silk show that the silk contains a significant crystalline component with a repetitive orthorhombic unit cell aligned along the fiber axis with dimensions of 5.9 Å × 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 30 publications
0
40
0
2
Order By: Relevance
“…The proposal that H-fibroin (pSX) n motifs form a network of Ca 2+ -stabilized β-domains as the principal toughening mechanism of caddisworm silk is supported by multiple lines of experimental evidence. First, infrared (IR) and NMR spectroscopy, as well as X-ray scattering studies, showed decreased β-structure when Ca 2+ was exchanged with Na + [ 7 , 11 , 12 ]. Second, Ca 2+ -depleted silk fibres behaved mechanically like weak elastomers, with the initial stiffness decreased to 1% of native silk fibres, with no yield-like strain softening and no strain cycle hysteresis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The proposal that H-fibroin (pSX) n motifs form a network of Ca 2+ -stabilized β-domains as the principal toughening mechanism of caddisworm silk is supported by multiple lines of experimental evidence. First, infrared (IR) and NMR spectroscopy, as well as X-ray scattering studies, showed decreased β-structure when Ca 2+ was exchanged with Na + [ 7 , 11 , 12 ]. Second, Ca 2+ -depleted silk fibres behaved mechanically like weak elastomers, with the initial stiffness decreased to 1% of native silk fibres, with no yield-like strain softening and no strain cycle hysteresis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we expanded the protein–core model to include a description of how water interacts with the protein core in webspinner silk in the absence of organic solvent and show that exposure to water alone results in a change in macroscopic silk structure and wetting properties. Alternatively, exposure to water may remove metals that stabilize the β-sheet structure, as found in caddisfly silk, and when these metal cations are removed, water can penetrate rigid serine-phosphate regions and solvate the protein structure [ 28 ]. This hypothesis will be probed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The ampholytic character of caddisfly H‐fibroin leads to the formation of complex coacervates during the silk formation stage141 (discussed in Section 7). The negatively charged phosphates are proposed to interact with Ca 2+ ions creating intra‐ and intermolecular bridges that promote subsequent folding into rigid domains similar to β‐crystalline regions in spider and silkworm silks 142. 143 Accordingly, the presence of Ca 2+ has been shown to play a crucial role in the structural and macroscopic mechanical properties of these silk fibers 144.…”
Section: Adhesivesmentioning
confidence: 99%